2022
DOI: 10.3346/jkms.2022.37.e233
|View full text |Cite
|
Sign up to set email alerts
|

mRNA COVID-19 Vaccine-Associated Subserosal Eosinophilic Gastroenteritis: A Case Report

Abstract: The World Health Organization declared coronavirus disease 2019 (COVID-19) a global pandemic in March 2020. Several vaccines have been developed to overcome the COVID-19 pandemic, and messenger RNA vaccines, commonly known as mRNA vaccines, were the first COVID-19 vaccines to be authorized in Korea. With the worldwide increase in vaccinations, reports of adverse reactions are increasing. However, to the best of our knowledge, there have been no reports of eosinophilic gastroenteritis (EGE) following mRNA vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…A systematic review [ 6 ] found that the mean duration from COVID-19 vaccination to the onset of R-IMID was 10.6 days, suggesting a temporal association between R-IMID and COVID-19 vaccination owing to the short time to onset. Reports of eosinophilia following COVID-19 mRNA vaccination [ 4 , 5 ] , including the present case, also showed a similar time span to onset as that of R-IMID. As COVID-19 vaccines have been administered to a large number of people worldwide, it is necessary to investigate lesser-known adverse events and develop immunological studies on post-vaccination biological reactions.…”
Section: Discussionsupporting
confidence: 77%
“…A systematic review [ 6 ] found that the mean duration from COVID-19 vaccination to the onset of R-IMID was 10.6 days, suggesting a temporal association between R-IMID and COVID-19 vaccination owing to the short time to onset. Reports of eosinophilia following COVID-19 mRNA vaccination [ 4 , 5 ] , including the present case, also showed a similar time span to onset as that of R-IMID. As COVID-19 vaccines have been administered to a large number of people worldwide, it is necessary to investigate lesser-known adverse events and develop immunological studies on post-vaccination biological reactions.…”
Section: Discussionsupporting
confidence: 77%
“…Inflammatory cytokines, autoimmune involvement, angiotensin-converting enzyme 2 downregulation, and eosinophil association have been suggested to be related to post-vaccine adverse reactions [ 14 ]. Eosinophilic diseases after COVID-19 vaccination included eosinophilic myocarditis [ 15 , 16 ], eosinophilic pneumonia [ 16 18 ], eosinophilic granulomatosis with polyangiitis [ 19 ], eosinophilic cellulitis [ 20 , 21 ], eosinophilic panniculitis [ 22 ], eosinophilic gastroenteritis [ 23 ] and NEAE [ 24 ]. Eosinophil responses are observed not only during COVID-19 infection but also during coronavirus vaccination [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although tissue biopsies of the upper and lower gastrointestinal tracts did not show prominent eosinophilic infiltrates or granulomas, pathological findings, including the gastrointestinal tract, alone cannot be used to exclude EGPA as a diagnosis [ 9 ]. In previous reports, there were several cases of eosinophil infiltration of the upper and lower gastrointestinal tracts triggered by COVID-19 infection or vaccination, but the detailed mechanism is unclear [ 10 , 11 ]. Furthermore, since no challenge test has been performed, the presence of latent asthma cannot be ruled out, which is another reason why EGPA remains a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%